Efficacy of Intravitreal Dexamethasone Implant in Patients of Uveitis Undergoing Cataract Surgery. (17th November 2019) - Gupta, Gaurav; Ram, Jagat; Gupta, Vishali; Singh, Ramandeep; Bansal, Reema; Gupta, Parul Chawla; Gupta, Amod
ABSTRACT: Purpose : To assess postoperative inflammation using laser flare photometer, following phacoemulsification with or without single intraoperative intravitreal dexamethasone implant in addition to standard of care, in patients of uveitis with cataract. Methods : Prospectively, 30 eyes with uveitic cataract were randomized into 2 groups (i) standard of care (SOC group) (ii) Dexamethasone implant (DEXA group). Both the groups underwent phacoemulsification with intraocular lens implantation and standard of care treatment for uveitis, but DEXA group additionally received intraoperative intravitreal dexamethasone implant. Patients were followed at least till 6 months. Results : DEXA group had significantly less postoperative flare (LFP values) (P<0.05) as compared to SOC group and also recovery of flare to preoperative value occurred much early in DEXA group. 37.5% cases developed CME in SOC group but none in DEXA group. Mean CMT (267.81±34.26μm) and final logMar BCVA (0.036±0.063) was significantly better in DEXA group ( p <0.04). Conclusions : Intraoperative intravitreal dexamethasone implant is a safe and effective option for preventing and managing the postoperative inflammation in uveitic cataract.